Cultivar-specific responses in red sweet peppers grown under shade nets and controlled-temperature plastic tunnel environment on antioxidant constituents at harvest. (1st March 2019) - Lekala, Chembi Solomon; Madani, Khalil Saber H.; Phan, Anh Dao Thi; Maboko, Martin Makgose; Fotouo, Helene; Soundy, Puffy; Sultanbawa, Yasmina; Sivakumar, Dharini
Highlights: Temperature controlled plastic tunnels improved the content of carotenoids in most sweet peppers. White shade nets influenced the accumulation of phenolic acids in sweet pepper cultivars. Both environments did not affect the marketable yield in sweet pepper cultivars. Ascorbic acid and vitamin C were higher under the temperature controlled plastic tunnels. Bound (B) and Free (F)-quercetin-3-glycoside and were higher under the white shade nets. Abstract: Antioxidant constituents such as carotenoids (capsanthin, phytoene, lutein, β-cryptoxanthin), polyphenols content ( p -coumaric, ferulic, p -hydroxybenzoic, caffeic acid, sinapic acid, and quercetin-3-glucoside) and marketable yield were investigated in 11 sweet pepper cultivars grown under controlled temperature plastic tunnel and white shade net. Marketable yield was not affected by either of the environments, while the interaction between cultivar and growing environment significantly affected the accumulation of antioxidant constituents. The principal component analysis illustrated that controlled temperature plastic tunnel improved the accumulation of carotenoid components and ascorbic acid and vitamin C content in most cultivars. On the contrary, white shade nets favoured the accumulation of phenolic compounds and ORAC activity in most cultivars. A strong correlation was noted between phytoene and carotenoid components in this study (capsanthin r  = 0.60; P  < 0.001; lutein r  = 0.75; P  < 0.001; β-carotene r  = 0.78; P  < 0.001) while ORAC correlated with phenolic compounds. Based on this study, it is possible to refine the choice of environment and cultivar to enhance individual antioxidant constituent groups to improve health benefits for consumers.